Effects of bariatric surgery on drug pharmacokinetics—Preclinical studies - Mercado, Angela; Pham, Anna; Wang, Zhijun; Huang, Wendong; Chan, Patrick; Ibrahim, Hajer; Gogineni, Hyma; Huang, Ying; Wang, Jeffrey (Frontiers in Pharmacology, 2023)
With the rising worldwide obesity rates, bariatric surgeries are increasing. Although the surgery offers an effective treatment option for weight loss, the procedure causes dramatic physiological and metabolic changes. Animal models in rodents provide a valuable tool for studying the systemic effects of the surgery. Since the surgery may significantly influence the pharmacokinetic properties of medications, animal studies should provide essential insight into mechanisms underlying changes in how the body handles the drug. This review summarizes research work in rodents regarding the impact of standard bariatric procedures on pharmacokinetics. A qualitative literature search was conducted via PubMed, the Cochrane Central Register of Controlled Trials (CENTRAL), and EMBASE. Studies that examined bariatric surgery's effects on drug pharmacokinetics in rodent models were included. Clinical studies and studies not involving drug interventions were excluded. A total of 15 studies were identified and assessed in this review. These studies demonstrate the possible impact of bariatric surgery on drug absorption, distribution, metabolism, excretion, and potential mechanisms. Pharmacokinetic changes exhibited in the limited pre-clinical studies highlight a need for further investigation to fully understand the impact and mechanism of bariatric surgery on drug responses.